ROS-Scavenging Enzymes as an Antioxidant Response to High Concentration of Anthracene in the Liverwort Marchantia polymorpha L. - Spinedi, Nahuel; Storb, Romina; Aranda, Elisabet; Romani, Facundo; Svriz, Maya; Varela, Santiago Agustin; Moreno, Javier E.; Fracchia, Sebastian; Cabrera, Juan; Batista-García, Ramón Alberto; Ponce de León, Inés; Scervino, j. Martin (MDPI, 2023)
Marchantia polymorpha L. responds to environmental changes using a myriad set of physiological responses, some unique to the lineage related to the lack of a vascular- and root-system. This study investigates the physiological response of M. polymorpha to high doses of anthracene analysing the antioxidant enzymes and their relationship with the photosynthetic processes, as well as their transcriptomic response. We found an anthracene dose-dependent response reducing plant biomass and associated to an alteration of the ultrastructure of a 23.6% of chloroplasts. Despite a reduction in total thallus-chlorophyll of 31.6% of Chl a and 38.4% of Chl b, this was not accompanied by a significant change in the net photosynthesis rate and maximum quantum efficiency (Fv/Fm). However, we found an increase in the activity of main ROS-detoxifying enzymes of 34.09% of peroxidase and 692% of ascorbate peroxidase, supported at transcriptional level with the upregulation of ROS-related detoxifying responses. Finally, we found that M. polymorpha tolerated anthracene-stress under the lowest concentration used and can suffer physiological alterations under higher concentrations tested related to the accumulation of anthracene within plant tissues. Our results show that M. polymorpha under PAH stress condition activated two complementary physiological responses including the activation of antioxidant mechanisms and the accumulation of the pollutant within plant tissues to mitigate the damage to the photosynthetic apparatus.